2005
DOI: 10.1021/bc049777y
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Self-Alkylation of Isotope-Coded Affinity Tag Reagents

Abstract: A pair of ICAT reagents, N-(13-iodoacetamido-2,2,3,3,11,11,12,12-octadeutero-4,7,10-trioxa-tridecanyl)biotinamide (8d, ICAT-d(8)) and N-(13-iodoacetamido-4,7,10-trioxa-tridecanyl)biotinamide (8c, ICAT-d(0)), and an alternative pair of ICAT reagents, N-(10-iodoacetamido-2,5,5,6,6,9-hexadeutero-4,7-dioxa-decanyl)biotinamide (8b, s-ICAT-d(6)) and N-(10-iodoacetamido-4,7-dioxa-decanyl)biotinamide (8a, s-ICAT-d(0)), were successfully synthesized. A mixture of sodium borohydride and cobalt(II) chloride reduced the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Besides, Ratner and Clarke showed that iodoacetic acid is able to alkylate the thioproline and that it results in the opening of the thiazolidine ring 18. This self‐alkylation side reaction has also been observed in standard Cys‐tagging techniques such as ICAT 20. When using the Boc‐ITC, it was found that this side reaction was prevented, since such side products were almost absent.…”
Section: Resultsmentioning
confidence: 84%
“…Besides, Ratner and Clarke showed that iodoacetic acid is able to alkylate the thioproline and that it results in the opening of the thiazolidine ring 18. This self‐alkylation side reaction has also been observed in standard Cys‐tagging techniques such as ICAT 20. When using the Boc‐ITC, it was found that this side reaction was prevented, since such side products were almost absent.…”
Section: Resultsmentioning
confidence: 84%
“…The synthesis of the diamine component 4 was completed following a literature procedure (Scheme 2) (28,29). Thus, two molar equivalents of diethylene glycol 7 were added in a 1,4addtion reaction to acrylonitrile.…”
Section: Resultsmentioning
confidence: 99%
“…Protein purification and its detection/localization are both essential components of proteomics and biomolecular research . Proteins are routinely purified utilizing affinity purification strategies with either chemical or biological tags . For efficient purification, either peptides or proteins are used as affinity tags .…”
Section: Introductionmentioning
confidence: 99%